Unraveling Evidence-Based Practices in Special Education. (August 2013) - Cook, Bryan G.; Cook, Sara Cothren
Evidence-based practices (EBPs) are instructional techniques that meet prescribed criteria related to the research design, quality, quantity, and effect size of supporting research, which have the potential to help bridge the research-to-practice gap and improve student outcomes. In this article, the authors (a) discuss the importance of clear understanding and communication regarding EBPs and what works in special education; (b) define EBPs and discuss how they are identified; (c) differentiate the term EBP from related terms such as research-based, best, and recommended practices ; (d) consider the purview of EBPs; and (e) present relevant caveats related to EBPs. The authors conclude by providing recommendations to facilitate special educators' clear and effectual thinking and communication about EBPs.